Energy loss analysis at the gland seals of a marine turbo-generator steam turbine - Kocijel, Lino (Array, 2020)
The paper presents an analysis of marine Turbo-Generator Steam Turbine (TGST) energy losses at turbine gland seals. The analyzed TGST is one of two identical Turbo-Generator Steam Turbines mounted in the steam propulsion plant of a commercial LNG carrier. Research is based on the TGST measurement data obtained during exploitation at three different loads. The turbine front gland seal is the most important element which defines TGST operating parameters, energy losses and energy efficiencies. The front gland seal should have as many chambers as possible in order to minimize the leaked steam mass flow rate, which will result in a turbine energy losses’ decrease and in an increase in energy efficiency. The steam mass flow rate leakage through the TGST rear gland seal has a low or negligible influence on turbine operating parameters, energy losses and energy efficiencies. The highest turbine energy efficiencies are noted at a high load – on which TGST operation is preferable.